2014
DOI: 10.17106/jbr.28.45
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of blood component flexibility using quartz crystal microbalance

Abstract: Quartz crystal microbalance (QCM) is widely used for the investigation of human blood mechanical properties, and shows high sensitivity for monitoring select dynamic processes, including red blood cell sedimentation and aggregation, coagulation, plasma protein absorption, as well as evaluating the bio-compatibility/affinity of different materials, etc. The present study provides a critical analysis of the challenges associated with data modelling and data interpretation, with respect to a QCM-based experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…-17 -2016). This behavior is in accordance with the fact that the fibrin fibers grow thicker and longer as the increase of coagulation time (Efremov et al 2014). At a constant fibrinogen concentration, the activator concentration determines the number of nucleation sites.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…-17 -2016). This behavior is in accordance with the fact that the fibrin fibers grow thicker and longer as the increase of coagulation time (Efremov et al 2014). At a constant fibrinogen concentration, the activator concentration determines the number of nucleation sites.…”
Section: Discussionsupporting
confidence: 83%
“…The fiber formation from fewer nucleation sites leads to fewer, but thicker, rigid and longer fibers at the low activator concentration (Blombäck et al 1994). In contrast, the rapid coagulation process, at high activator concentration, leads to many thin and small fibrin fibers that expose a relative larger area to the surrounding liquid and thus are considered more flexible (Efremov et al 2014). As a consequence, the low-density network results in a less frequency shift at the high TP concentration as shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In previous work [ 11 , 12 ], the effect of fibrinogen concentration on qualitative and quantitative viscoelastic changes during clot formation activated using a partial thromboplastin has been shown using QCM. In addition to measuring the activated partial thromboplastin time (aPTT), this method allowed the quantitative characterisation of fibrinogen concentrations as well as a qualitative characterisation of the properties of the forming clot in a single test [ 18 ], which usually requires two independent tests. Hussain et al [ 17 , 19 ] later reported a similar use of QCM in measuring clotting using the same aPTT assay for different fibrinogen concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…An unloaded (in-air) QCM sensor is typically characterised by a high quality factor with a resonant frequency ( f air ) ≈5 MHz and half bandwidth ( Γ air ) ≤30 Hz. In this article, the mechanical properties of a TF-activated plasma sample loaded on the sensor were investigated with a mathematical model developed [ 18 ] by means of an effective elasticity ( μ t ),effective mass density ( M t ) and resulting rigidity factor (RF) calculated using the shifts of resonance peak characteristics, Δ f and Δ Г , with respect to their “in-air” values. Briefly, QCM is used to investigate the effect of TF activation for coagulation and show that the developed model relates differences in TF concentration to changes in the qualitative nature of the formed clot.…”
Section: Introductionmentioning
confidence: 99%
“…QCM is a kind of acoustic sensors which has been widely used [ 15 , 16 , 17 , 18 , 19 ], frequency and dissipation are the two major properties which can be measured and traced. Frequency shift reflects the change of mass loaded on the sensor [ 20 , 21 , 22 ], while the dissipation factor gives viscoelastic information of the attached layer oscillating with QCM [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%